Empowerment Of Child-Friendly Class Management Based On Character For Early Child Teachers At Aisyah Paud Pondok Kelapa, Central Bengkulu Regency - Benriyanti, Rita Prima; Mayasari, Henni; Fadilla, Rohayu (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Not all Early Childhood Education schools Empowerment of Child-Friendly Classroom Management Based on Character for PAUD Teachers at PAUD Aisyah Pondok Kelapa, Central Bengkulu Regency, especially at PAUD Aisyah, Central Bengkulu, this is one of the reasons Lecturers and students of Dehasen University Bengkulu to carry out Community Service (PKM) activities. The aim is to analyze how to empower child-friendly class management based on character by PAUD teachers in Central Bengkulu Regency. From the results obtained in this PKM activity, Kindergarten teachers gain knowledge about child-friendly and character-based class management and Kindergarten teachers become more creative in managing child-friendly and character-based classes so that children do not get bored during the teaching and learning process.